Cotrimoxazole guidelines for infants who are HIV-exposed but uninfected: a call for a public health and ethics approach to the evidence. Issue 8 (August 2022) - Daniels, Brodie; Kuhn, Louise; Spooner, Elizabeth; Mulol, Helen; Goga, Ameena; Feucht, Ute; Essack, Sabiha Y; Coutsoudis, Anna
Summary: WHO first recommended cotrimoxazole prophylaxis for all infants who are HIV-exposed but uninfected (HEU) in 2000, given the ability of this treatment to prevent mortality from pneumocystis pneumonia in adults living with HIV. Over the last 21 years, evidence has been generated from the use of cotrimoxazole prophylaxis in infants who are HEU, including two randomised controlled trials, which have shown no clinical benefit and an increase in antibiotic resistance and microbiome dysbiosis. Additionally, improvements in health care over the last two decades in terms of antiretroviral treatment and prophylaxis for mothers and infants, and notably improved vaccination programmes, have substantially reduced the risk of HIV transmission and the overall morbidity and mortality of infants who are HEU from pneumonia and diarrhoeal diseases. Here, we highlight these changes in health care alongside the unchanged cotrimoxazole prophylaxis guidelines and call for a change in these guidelines on the basis of a public health and ethics approach.